Computed Tomografi Angiografi (CTA) Pada Kasus Aneurisma Cerebral : Literature Review - Kusnanto, Kusnanto (Poltekkes Kemenkes Semarang, 2025)
Background: A cerebral aneurysm is a sac or balloon in the artery within the subarachnoid space formed due to hemodynamic stress or turbulent flow. One method to confirm the diagnosis of a cerebral vascular aneurysm is cerebral CT scan angiography. CT Scan Angiography has great potential in vascular studies because of its sensitivity in detecting aneurysms. This research aims to analyze the results of angiography examinations using the CT scan modality in identifying cerebral aneurysms.Methods: This research is a literature-based study that uses secondary data from references to previous research, including literature reviews from textbooks and journal articles related to CT Scan Angiography in cases of cerebral aneurysm.Results: The expected results of this study are to determine the level of accuracy of angiographic examination with CT scan modalities in helping to establish a better diagnosis. The sensitivity of 3D CT Angiography examination in cerebral aneurysm cases is 67% and 70%.Conclusions: This research was conducted in the Radiology Department Room at Hospital X. Analysis of the results of Computed Tomography Scan Angiography (CTA) in Cerebral Aneurysm cases shows the results of the Aneurysm and bone structure clearly and can help make the right decision in surgery.